Effect of Pain Medication Choice on Emergency Room Visits for Pain after Ambulatory Laparoscopic Cholecystectomy. Issue 8 (August 2015) - Reddy, Vemuru Sunil K.; Brown, Joshua D.; Ku, Benson; Gilchrist, Brian F.; Farkas, Daniel T.
Inadequate pain control after ambulatory surgery can lead to unexpected return visits to the hospital. The purpose of this study was to compare patients based on which medications they were prescribed and to see whether this affected the rate of return to the hospital. A retrospective chart review of patients who underwent ambulatory laparoscopic cholecystectomy between January 2009 and December 2013 was performed. Patients were divided into two groups based on the pain medication prescribed after surgery: Opioids and nonopioids. Patients returning to the Emergency room (ER) within seven days were evaluated. If no complication or other diagnosis was identified, the patient was considered to have returned for inadequate pain control. The two groups were statistically compared with each other using Fisher's exact chi-squared test. A total of 749 patients underwent laparoscopic cholecystectomy during the study period: 180 (25.2%) were prescribed opioids, whereas, 560 (74.8%) were prescribed nonopioids. In the nonopioid group, 14 (1.9%) returned to the ER for pain, whereas no patient in the opioid group returned for pain. This difference was statistically significant ( P = 0.027). In conclusion, patients who were given opioid pain medications after ambulatory laparoscopic cholecystectomy were less likely to return to the ER for pain. This implied that opioids were better at pain control and helped avoid the costs of unnecessary ER visits. Future research should be aimed at more direct measures of pain control, as well as the role of opioids after inpatient surgery.